2004
DOI: 10.1111/j.1365-2036.2004.01888.x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin in the treatment of patients with non‐alcoholic steatohepatitis

Abstract: SUMMARYBackground: Increased insulin resistance is the major pathogenic mechanism in the development of nonalcoholic steatohepatitis. Aim: To investigate the therapeutic effect of metformin, a well-known insulin-sensitizing agent, in the treatment of non-alcoholic steatohepatitis. Methods: Thirty-six patients with non-alcoholic steatohepatitis were randomized into two groups. The first group was given lipid and calorie-restricted dietary treatment alone, and the second group was given metformin 850 mg b.d. plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
260
0
15

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(285 citation statements)
references
References 26 publications
5
260
0
15
Order By: Relevance
“…Early small, open-label studies demonstrated a reduction in insulin resistance and aminotransferases [106][107][108] but no significant improvement in liver histology. 107,108 An open-label trial consisting of 110 patients with NASH received either metformin 2 grams/day (55 patients), vitamin E 800 IU/day (28 patients) or dietary-induced weight loss (27 patients) for 12 months. 109 Aminotransferases improved more with metformin than with vitamin E or diet alone.…”
Section: Metforminmentioning
confidence: 99%
“…Early small, open-label studies demonstrated a reduction in insulin resistance and aminotransferases [106][107][108] but no significant improvement in liver histology. 107,108 An open-label trial consisting of 110 patients with NASH received either metformin 2 grams/day (55 patients), vitamin E 800 IU/day (28 patients) or dietary-induced weight loss (27 patients) for 12 months. 109 Aminotransferases improved more with metformin than with vitamin E or diet alone.…”
Section: Metforminmentioning
confidence: 99%
“…13 Histological Response. Two randomized trials showed no effect 8,14 on histology and one open-label trial showed improvement only in ballooning. 13 One study described histological improvement, 7 but the comparator arm did not undergo end-of-treatment biopsy, precluding definitive conclusions.…”
Section: Efficacy Outcomes In Nashmentioning
confidence: 99%
“…Human studies have documented a reduction in aminotransferases with metformin. [6][7][8][9][10][11] However, alanine aminotransferase (ALT) breakthrough was reported, 12 suggesting that there is no sustained effect. Other 1-year trials showed no overall significant reduction in ALT values.…”
Section: Efficacy Outcomes In Nashmentioning
confidence: 99%
See 1 more Smart Citation
“…Since insulin resistance has been regarded as a risk factor for the progression of liver disease and, moreover, preliminary observations in patients with NASH have shown improvement in liver histology following body weight loss or treatment with insulin sensitizing agents [85][86][87]; further research is needed to disclose the specific role of insulin resistance in CLD. To define the specific roles played by TNF-α and acquired GH resistance in the impairment of glucose metabolism, prospective studies on a large series of patients with CLD are also warranted, grouping patients according to the various aetiologies to better discriminate the effects of aetiologic factors with respect to tissue injury.…”
Section: Discussionmentioning
confidence: 99%